Respuesta :

Answer :

  • y = (1/6)*In(x - 7)/6 + C

Explanation :

multiply both sides by dx

  • (dy/dx)dx = (1/(6x -42))*dx
  • dy = (1/(6x -42))*dx

now, integrate both sides of the equation

  • y = ∫(1/(6x -42))*dx

to integrate the RHS,use u- substitution such that u = 6x -42 making du = 6*dx or dx = du/6 .

substituting the value of dx in the above integral ,

  • y = ∫(1/u)(1/6) du
  • y = 1/6 ∫(/u) du
  • y = (1/6) *Inlul + C
  • y = (1/6)*Inl(6x - 42)| + C

or

  • y = (1/6)*In(x - 7)/6 + C